(untitled) (Al-Mukhtar Journal of Legal Science, 2024)
The goal of this study is to explain what islam had come of guarantees which constiutes community from corruption، and to find-out the precautionary measures which the islamic legislative performed ، inorder to put an end to the phenomenon of corruption and not to obey what god oredred with ، and to abandoning islamic values ​​such as integrity، honesty، truthfulness، justice and transparency, begenning from the protection methods from corruption which is represented in reforming the creed and intensifying the discourse of encouragement for integrity and intimidation from corruption and its consequences، in addition to legislating penalties and holding accountable anyone who commits the crime، whether in libyan criminal legislation or in the system of oversight bodies specialized in combating corruption in libya ، and the range of texts compatibility in the libyan legislation to coincide with the islamic legislation rules . and explaining the similarities and differences between themin combatig corruption crimes which it is eating away at the body of the nation and is getting worse until it has reached critical levels، where society is threatened with collapse.